KAJIAN HUKUM ISLAM TERHADAP CHILDFREE (TANPA ANAK ATAU BEBAS ANAK) OLEH PASANGAN SUAMI ISTRI YANG TELAH MENIKAH - URAY FARID HERDIANTO NIM. A1011191204 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract Regarding the phenomenon of childfree, Indonesian people have started to talk about this childfree phenomenon ever since an influencer or YouTuber named Gita Savitri and her husband openly revealed on their social media that they would take a childfree attitude and raise pros and cons in Indonesian society regarding the concept of childfree itself. Because basically the concept of childfree is the attitude taken by married couples not to have children or offspring due to personal reasons not because having certain diseases or physical limitations. On that basis, the concept of childfree is in stark contrast to Indonesian culture and the Islamic religion. The problem statement that is used as the focus of the study is